FGF2 Attenuates Neural Cell Death via Suppressing Autophagy after Rat Mild Traumatic Brain Injury. (17th October 2017) - Tang, Chonghui; Shan, Yudong; Hu, Yilan; Fang, Zhanjian; Tong, Yun; Chen, Mengdan; Wei, Xiaojie; Fu, Xiaojun; Xu, Xinlong
Abstract : Traumatic brain injury (TBI) can lead to physical and cognitive deficits, which are caused by the secondary injury process. Effective pharmacotherapies for TBI patients are still lacking. Fibroblast growth factor-2 (FGF2) is an important neurotrophic factor that can stimulate neurogenesis and angiogenesis and has been shown to have neuroprotective effects after brain insults. Previous studies indicated that FGF2's neuroprotective effects might be related to its function of regulating autophagy. The present study investigated FGF2's beneficial effects in the early stage of rat mild TBI and the underlying mechanisms. One hundred and forty-four rats were used for creating controlled cortical impact (CCI) models to simulate the pathological damage after TBI. Our results indicated that pretreatment of FGF2 played a neuroprotective role in the early stage of rat mild TBI through alleviating brain edema, reducing neurological deficits, preventing tissue loss, and increasing the number of surviving neurons in injured cortex and the ipsilateral hippocampus. FGF2 could also protect cells from various forms of death such as apoptosis or necrosis through inhibition of autophagy. Finally, autophagy activator rapamycin could abolish the protective effects of FGF2. This study extended our understanding of FGF2's neuroprotective effects and shed lights on the pharmacological therapy after TBI.